Exploring Abstract Writing in the EFL Undergraduate Theses: A Construction-based Analysis - Nurjati, Nunung; Bandjarjani, Wahju (Anaphora : Journal of Language, Literary, and Cultural Studies, 2023)
An abstract is considered a miniature of a whole series of scientific works. The contents of each chapter in the entire scientific result must be represented in an abstract. However, various abstracts have different structures from one another. Thus, writers of scientific papers have a choice with the appropriate abstract form, but at the same time, they also have problems choosing which structure to use. Therefore, this study aimed to explore the designs of abstract writing from the EFL undergraduate students who different academic advisors guide. A qualitative method with content analysis was employed in this study by examining students' scientific work under the guidance of other supervisors in the form of theses with a focus on the abstract part. As a result of the research, it has been identified that most abstracts employed informative type and structured format with different compositions. In addition, the research results would contribute to the description of the abstract structure utilized by the students as the object of this research. Based on these findings, it can be suggested that understanding abstract construction can be employed by introducing different types of abstract and their format in academic writing courses or research methodology. The lecturer can apply the strategy of compiling leading questions for each abstract type. Answering the leading questions has guided the flow of abstract writing ideas in a thesis.